An Enhanced Reduced Basis Method for Wideband Finite Element Method Simulations - Szypulski, Damian; Fotyga, Grzegorz; Mrozowski, Michal (IEEE access, 2019)
In this paper, we present a novel strategy for selecting expansion points in the reduced basis method. A single computation of the error estimator is used to select a few expansion points in the multi-parameter space simultaneously. The number of selected points is determined adaptively, based on the accuracy of the current reduced model. The reliability and efficiency of this proposed approach are illustrated by numerical tests considering real-life structures, including dielectric resonator filter, H-plane filter, and four-pole dielectric-loaded cavity filter.